2013 IEEE International Conference on Acoustics, Speech and Signal Processing 2013
DOI: 10.1109/icassp.2013.6639282
|View full text |Cite
|
Sign up to set email alerts
|

Zero resource graph-based confidence estimation for open vocabulary spoken term detection

Abstract: In this paper the use of acoustic similarity of speech intervals for generating improved confidence scores for spoken term detection (STD) is investigated. A procedure based on acoustic dotplots which requires no training data is deployed for discovering similar speech intervals. A graph based random walk algorithm incorporates acoustic similarity of hypothesized term occurrences for improving the corresponding confidence scores. The proposed approach is evaluated in an open vocabulary STD task defined on a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The figure-of-merit [37] of the original and fused systems were 38.7% and 43.7%, respectively-a 13% relative performance improvement from augmenting the core STD system with zero resource techniques. For details, see [39].…”
Section: Improving Abstractearch Using Lexical Discoverymentioning
confidence: 99%
“…The figure-of-merit [37] of the original and fused systems were 38.7% and 43.7%, respectively-a 13% relative performance improvement from augmenting the core STD system with zero resource techniques. For details, see [39].…”
Section: Improving Abstractearch Using Lexical Discoverymentioning
confidence: 99%
“…In the experiments on lectures for a course taught by a single instructor, 21.2% relative improvement for speaker independent recognition was obtained. It also yielded 13% relative improvement for a set of OOV queries on audio recordings of McGill course lectures [193] with several speakers [185], and 6.1% relative improvements on broadcast news with many speakers [184]. The graph-based approach with random walk was also shown to outperform the exemplar-based approach with examples from PRF [181].…”
Section: E Graph-based Approachmentioning
confidence: 93%
“…Another way to exploit the graph structure is using the random walk [181]- [183], [185], which does not use any labelled data. The basic idea is that the hypothesized regions (nodes) strongly connected to many other hypothesized regions (nodes) with higher/lower confidence scores on the graph should have higher/lower scores.…”
Section: E Graph-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the original detection scores, which are normally the posterior probabilities [14] of keywords at detected locations, might not be robustly estimated in adverse conditions. Thus, various approaches has been proposed to rescore the KWS detections [15][16][17][18][19][20][21][22][23]33].…”
Section: Introductionmentioning
confidence: 99%